1980
DOI: 10.1016/s0006-3495(80)84960-5
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of subunit assembly and ligand binding in human hemoglobin

Abstract: An extensive and self-consistent set of thermodynamic properties has recently been established for the coupled processes of subunit assembly and ligand binding (oxygen and protons) in human hemoglobin. The resulting thermodynamic values permit a consideration of the possible sources of energetic terms accounting for stability of the tetrameric quaternary structures at different stages of ligation, and of the possible sources of cooperative energy. The analysis indicates that: (a) The change in buried surface a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
51
0

Year Published

1982
1982
1997
1997

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 41 publications
7
51
0
Order By: Relevance
“…(Oxidation of HbI results in a hemichrome species that shows extensive dissociation, with an association constant of about 3 ϫ 10 3 M Ϫ1 at pH 7.0 (29).) Thermodynamic coupling between ligation and subunit dissociation (14) predicts that given a tighter assemblage in the deoxy state compared with the oxy state, oxygen affinity of HbI should increase upon subunit dissociation. To test this prediction, we carried out oxygen binding experiments on solutions with hemoglobin concentrations between 0.2 and 8 M heme.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Oxidation of HbI results in a hemichrome species that shows extensive dissociation, with an association constant of about 3 ϫ 10 3 M Ϫ1 at pH 7.0 (29).) Thermodynamic coupling between ligation and subunit dissociation (14) predicts that given a tighter assemblage in the deoxy state compared with the oxy state, oxygen affinity of HbI should increase upon subunit dissociation. To test this prediction, we carried out oxygen binding experiments on solutions with hemoglobin concentrations between 0.2 and 8 M heme.…”
Section: Resultsmentioning
confidence: 99%
“…In human hemoglobin, cooperativity results primarily from quaternary constraints in which the tight deoxy assemblage lowers the intrinsic subunit oxygen affinity, and binding of subsequent ligands leads to a stepwise reduction of these constraints (14). Analysis of equilibrium binding data has suggested that the fourth ligand is bound with higher affinity than isolated chains, an effect termed quaternary enhancement (13).…”
mentioning
confidence: 99%
“…First, this number cannot strictly be compared with experimental values for the Ro --To transition,-since there are tertiary conformational changes upon removing the 4 ligands from the R4 molecule, which might affect the buried surface area (30,31,37) (as well as the position of the transition state). Second, the value of 25 cal mold A-2 could be in significant error (38).…”
mentioning
confidence: 99%
“…A series ofstudies over the past 7 years, of which this work forms a part, has been aimed toward resolving the essential energetic aspects of the hemoglobin mechanism and of correlating the thermodynamic and structural information (cf. refs [15][16][17][18][19][20]. Identification of the sites of regulatory energy change within the hemoglobin molecule, as provided by the results ofthis study, lies at the core of this problem.…”
mentioning
confidence: 99%